COMPARATIVE STUDY OF SPEECH ACT ADVICE-GIVING IN INDONESIAN CULTURE AND AMERICAN CULTURE FOUND IN TELEVISION SERIES - Nida, Camalia Fatih (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
In line with the growth of interests at the study of cross-cultural pragmatics, however, the study comparison between Indonesian and American culture has not been presented adequately in the terms of advice-giving. Advice-giving strategies in Indonesian culture and American culture with the focus on a close relationship domain are the focus of this research. Specifically, it compares the advice-giving of native Indonesian speakers in television series entitled ‘Tetangga Masa Gitu?’ on Net TV with native English American characters which depicted on NBC TV channel entitled ‘Friends’. Moreover, this study attempts to identify the similarities and differences between both objects. The data are from six episodes of the two. Qualitative research method is used to conduct this research. This research describes the pattern of the advice-giving speech act realization from the characters of two television series and compares both cultures. The findings show that advice giving in Indonesian and American cultures is classified into giving support, giving suggestions, and stating prohibition. Generally, advice-giving in Indonesian culture tends to be indirect since it is crucial to save hearer's face. In American culture, direct strategies are mostly chosen as it is a matter to show one’s freedom of self-expression. Most of advice-giving in American cultures include related facts to strengthen the illocutionary force.